Human rights in a secularized society - Willem Jacobus Eijk (Chrześcijaństwo-Świat-Polityka)
The article addresses the issue of the attitude of the Catholic Church towards the doctrine of human rights. This doctrine was originally developed on the grounds of Catholic reflection accompanying the phenomenon of colonial conquests. Its use in the context of the Peace of Westphalia and the French Revolution caused the Church to distance itself from the doctrine. The return came with the person of John XXIII and the Second Vatican Council. Pope John Paul II proved to be a particularly important promoter of human rights. However, during the period in which the Church officially lent support to the doctrine of human rights, significant changes occurred in the Western world due largely to secularization. As a result, the way human rights were interpreted changed fundamentally. This has caused the secular understanding of human rights that dominates Western politics to be increasingly distant not only from the Catholic interpretation of them, but also from their original expression in the UN Universal Declaration.